Fabrication and characterization of biodegradable composite film from banana stem - Lim, Rwi Hau (2009)
The diverse utilization of packaging films from bio-based compounds has received so much attention lately due to the fact that they are readily biodegradable. Banana stem fiber was subjected to acid hydrolysis and three types of film samples, banana stem fiber-chitosan, cassava starch-chitosan and banana stem fiber-cassava starch-chitosan were fabricated with the addition of PEG400. The film samples were later characterized in terms of their morphological and physical properties through FTIR, TGA, DSC and AFM. Analytical results showed that the three compounds used were almost identical in structure and therefore the miscibility between them was of considerable degree. Results also showed that the thermal stability of the three films was significantly noteworthy to be used as a packaging material. The addition of bio-fibers also affected the thermal and mechanical properties of the film samples. Thus, this study gave a new in-depth look into the usage of biofibers as reinforcing agents of biodegradable films of low thermal and mechanical properties.